A rare cause of obstructive jaundice: Fasciola hepatica mimicking cholangiocarcinoma - Orçun YALAV,; Özgür YAĞMUR,; Abdullah ÜLKÜ,; Atılgan Tolga AKCAM,; Hüsnü SÖNMEZ, (Turkish Journal of Gastroenterology, 2019)
-